Dysbiosis of Cervical and Vaginal Microbiota Associated With Cervical Intraepithelial Neoplasia - Lin, Suibin; Zhang, Bin; Lin, Yixia; Lin, Yueping; Zuo, Xiaoyu (Frontiers in Cellular and Infection Microbiology, 2022)
Cervical intraepithelial neoplasia (CIN) is a precancerous condition inducing local lesions on the surface of the squamocolumnar junction of the cervix. Despite vaginal microbiota, the role of cervical microbiome involved in CIN was limited studied. We aimed to synchronously characterize the dysbiosis associated with CIN in both cervix and vagina in a Chinese population. Both cervical and vaginal microbial profiling from 60 CIN women and 60 healthy women were conducted. 16S rRNA sequencing was adopted. By comparing the microbial profiles between different parts of the reproductive tract, our results demonstrated an increased shift of microbial diversity in cervix compared with that in vagina for CIN patients, specifically in CIN 1. Less dysbiosis was found between CIN patients and controls, either in vagina or cervix. The microbial community may be modulated by the onset of sexual activity, a known clinical risk factor for cervical neoplasia. Distinct patterns of perturbated bacteria were found in vaginal and cervical microbiota, in which reduced Actinobacteria-related OTUs and increased Proteobacteria-related OTUs were found in vagina and cervix, respectively. A good agreement between the direction of the top-significant perturbated OTUs were observed between vaginal and cervical microbiome, suggesting a potential microbial migration in the reproductive tract. Enriched genera such as Sphingomonas and Stenotrophomonas were found in cervical microbiota associated CIN. Multivariate analysis revealed Comamonas, Rhizobium, and Psedomonas as independent genera contributing to CIN in cervix. In summary, This study revealed the perturbation of microbiota in the presence of CIN, and demonstrated a distinct pattern of characteristic bacteria community between vargina and cervix involved in the development of CIN.